Mechanism of Action Potential Prolongation During Metabolic Inhibition in the Whole Rabbit Heart - Mačianskienė, Regina; Martišienė, Irma; Navalinskas, Antanas; Treinys, Rimantas; Andriulė, Inga; Jurevičius, Jonas (Frontiers in Physiology, 2018)
Myocardial ischemia is associated with significant changes in action potential (AP) duration, which has a biphasic response to metabolic inhibition. Here, we investigated the mechanism of initial AP prolongation in whole Langendorff-perfused rabbit heart. We used glass microelectrodes to record APs transmurally. Simultaneously, optical AP, calcium transient (CaT), intracellular pH, and magnesium concentration changes were recorded using fluorescent dyes. The fluorescence signals were recorded using an EMCCD camera equipped with emission filters; excitation was induced by LEDs. We demonstrated that metabolic inhibition by carbonyl cyanide-p-trifluoromethoxyphenylhydrazone (FCCP) resulted in AP shortening preceded by an initial prolongation and that there were no important differences in the response throughout the wall of the heart and in the apical/basal direction. AP prolongation was reduced by blocking the ICaL and transient outward potassium current (Ito) with diltiazem (DTZ) and 4-aminopyridine (4-AP), respectively. FCCP, an uncoupler of oxidative phosphorylation, induced reductions in CaTs and intracellular pH and increased the intracellular Mg2+ concentration. In addition, resting potential depolarization was observed, clearly indicating a decrease in the inward rectifier K+ current (IK1) that can retard AP repolarization. Thus, we suggest that the main currents responsible for AP prolongation during metabolic inhibition are the ICaL, Ito, and IK1, the activities of which are modulated mainly by changes in intracellular ATP, calcium, magnesium, and pH.